MLA 72-86 - Mineral Resources Of The Pryor Mountain Wilderness Study Area, Burnt Timber Canyon, And Big Horn Tack-On Study Areas, Carbon County, Montana And Big Horn County, Wyoming ? Summary - Leon E. Esparza (The National Institute for Occupational Safety and Health (NIOSH), 1986)
In 1985, at the request of the U.S. Bureau of Land Management, the U.S. Bureau of Mines studied the 16,927-acre Pryor Mountain Wilderness Study Area (MT-067-206), part of the 3,955-acre Burnt Timber Canyon Wilderness Study Area (MT-067-205), and part of the 4,550-acre Big Horn Tack-On Wilderness Study Area (MT-067-207) to evaluate their identified mineral resources. The Burnt Timber and Big Horn Tack-On study areas contain 3,430 and 2,550 acres, respectively. The three areas are in Carbon County, MT, and Big Horn County, WY, about 13 miles north of Lovell, WY. No identified resources exist in any of the study areas. Bureau of Mines personnel reviewed literature, searched county mining records and examined prospects, claims, and mineralized areas to determine whether identified mineral resources existed. The three study areas are within the Pryor Mountain unorganized mining district. U.S. Department of Energy production records indicate there were 223,000 pounds of uranium oxide (U308) and 236,000 pounds of vanadium pentoxide (V205) produced from 19 properties within the mining district. The average ore grade was 0.36 percent [3,600 ppm (parts per million)] U308 and 0.416 percent (4,160 ppm) V20S. Only the Pryor Mountain study area has current claims, the 50 claims of the S0S group.